Peran Desain Interior dalam Menunjang Kenyamanan Belajar Anak di RA Bi Al-Nazhar - Armanila Armanila; Elfidayati Elfidayati; Alya zahro Azhari; Devi Sinta; Syariah Hafizhoh (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
The interior design describes one of the interior planning systems that functions to stay away from the state of the area by producing an atmosphere and image that fulfills the comfort, safety, and physical and spiritual needs of its users, without neglecting the aesthetic aspects of the area. Layout planning and interior design of the building. This research was attempted to identify the position of Raudahatul Athfal Bi Al-Nazhar in the interior design which is very meaningful because a good and attractive spatial layout can be more enthusiastic, not only providing comfort for children in learning and learning. So that all aspects of children's growth can grow better. This research uses qualitative research. The results of this research show that the condition of the study room will affect the quality of education. An unorganized space will definitely make children lose motivation to learn. beautiful, and also organized, integrated with the theme of learning, will definitely facilitate the learning of teachers and children. Not only that, a good classroom presses children to be more active in every learning activity. Keywords: interior design, children's learning comfort References Achmad, N. (2016). Pelaksanaan Proses Belajar Mengajar di Fakultas ABC. The 3rd University Research Colloquium 2016, 1–11. https://publikasiilmiah.ums.ac.id/bitstream/handle/11617/6693/1. Nur Achmad.pdf?sequence=1 Deli, M., & Kunci, K. (2017). Irwansyah, Analisis Ornamen Interior Pada 21. Jurnal Proporsi, 3, 21–32. https://mail.e- journal. potensiutama. ac.id/ojs/index.php/PROPORSI /article/view/550/718 Fasilitas Ruang Belajar Taman Kanak-Kanak Terhadap Perkembangan Kreatifitas Anak. Jurnal Seni Dan Reka Rancang: Jurnal Ilmiah Magister Desain, 1(2), 261. https://doi.org/10.25105 /jsrr.v 1i2.6738 Fathurohman, O. (2017). Hakikat Bermain Dan Permainan Anak Usia Dini Di Pendidikan Anak Usia Dini (PAUD). aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 27–36. Ilmianti, A. (n.d.). Adln - perpustakaan universitas airlangga. 1–5. Imroatun, I. (2014). Permainan Tradisional Sebagai Pembelajaran Kecakapan Sosial Bagi Anak Usia Dini. Jurnal Sains Psikologi, 3(1), 1–11. Nadjih, D., & Imroatun, I. (2016). Hadits Tentang Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 51–64. Najib, M. (2018). Model Manajemen PAUD Berdaya Saing Studi Pada Lembaga PAUD Islam Terpadu Al-Ikhlas Bumiayu Kabupaten Brebes. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(2), 125–136. Prasetya, N. (2012). Kajian Aspek Interior Ruang Belajar Dan Bermain PadaTaman Kanak-Kanak Di Surakarta.10(1), 23–32. https://doi.org/10.9744/interior.10.1.23-32 Pratiwi, D. A., Adhitama, G. P., & Sari, N. (2020). Penyesuaian ruang dalam membentuk behavioral setting lingkungan pembelajaran di ruang kelas TKQ Ulul Ilmi – MUI Kota Bandung. JurnalItenas Rekarupa, 5(2), 2019. Rahman, M. F. N., & Jumino. (2020). Peran Desain Interior Dalam Menunjang Kenyamanan Pengguna di Perpustakaan Badan Pusat Statistik Provinsi Jawa Tengah. Anuva, 4(1), 81–98. Ramadhani, I., & Utama, U. P. (2016). Keterkaitan Elemen Interior Tempat. JurnalProporsi, 1, 132. http://ejournal.potensiutama.ac.id/ ojs/ index.php/PROPORSI/article/view/519/65 Retno, D. (n.d.). Desain Interior. 148, 148–162. Sindunoto, H. (2013). Pengaruh Desain Interior Kelas Terhadap Minat Belajar Siswa. DimensiInterior, 11(1), 22– 30. https://doi.org/10.9744/interior.11.1.2 2-30 Sriti Mayang Sari. (2004). Peran Warna Interior Terhadap Perkembangan Dan Pendidikan Anak Di Taman KanakKanak. 2(1), 22–36. http://puslit2.petra.ac.id/ejournal/inde x.php/int/article/view/16244 Tema, D., Dan, C., & Islami, B. (n.d.). Desain interior kb dan tk ta’miriyah dengan tema ceria dan bernuansa islami untuk meningkatkan potensi anak usia dini. Thenius, H. P., Joedawinata, A., & Asmarandani, D. (2019). Kajian Dampak Elemen Interior Pada Fasilitas Ruang Belajar Taman Kanak-Kanak Terhadap Perkembangan Kreatifitas Anak. Jurnal Seni Dan Reka Rancang: Jurna lIlmiah Magister Desain, 1(2), 261. https://doi.org/10.25105 /jsrr.v 1i2.673 wahyu widodo. (2016). Wujud Kenyamanan Belajar Siswa. Euphytica, 18(2), 22280. http://dx.doi.org/10.1016/j.jplph.2009.07.006%0A Wulan Astrini. (2005). Pengaruh Interior Ruang Belajar Dan Bermain Terhadap Kognitif Afektif Dan Psikomotorik Anak Di Tk Negeri Pembina Malang. Dimensi Interior, 3(1), 1–16.